Effects of Chronic Voluntary Alcohol Drinking on Thiamine Concentrations, Endoplasmic Reticulum Stress and Oxidative Stress in the Brain of Crossed High Alcohol Preferring Mice - Xu, Hong (Neurotox Res, 2019)
Chronic alcohol drinking can damage the central nervous system via many mechanisms. One of these may involve a deficiency of an essential nutrient, thiamine, as a result of chronic alcohol exposure. Although thiamine deficiency (TD) has often been linked to the neuropathology of alcohol-related brain damage, the underlying mechanisms remain to be investigated. The crossed High Alcohol Preferring (cHAP) mice prefer alcohol to water when they have free access. In this study, we used cHAP mice to determine the effect of chronic voluntary alcohol exposure on thiamine levels and neuropathological changes in the brain. The male cHAP mice were given free-choice access to 10% ethanol (EtOH) and water for 7 months, sacrificed, and thiamine concentrations in the blood plasma and brain were determined by liquid chromatography–mass spectrometry (LC-MS). The expression of thiamine transporters was examined by immunoblotting. In addition, oxidative stress, endoplasmic reticulum (ER) stress, active caspase-3 dependent apoptosis, and neurogenesis in the brain were evaluated. The results indicated that chronic alcohol exposure decreased thiamine levels and thiamine transporters, and increased oxidative stress, ER stress, and neuronal apoptosis in the brains. Interestingly, alcohol exposure also stimulated neurogenesis in the hippocampus which may serve as a compensatory mechanism in response to alcohol-induced brain damage. Our data have demonstrated that cHAP mice are a useful model to study the interaction between chronic alcohol consumption and TD, as well as TD’s contributions to the neuropathological processes resulting in alcohol-related brain damage.